The handmaid's tale. Season two - Barker, Mike, 1966-; Skogland, Kari; Moss, Elisabeth, 1983-; Strahovski, Yvonne, 1982-; Minghella, Max, 1985-; Atwood, Margaret, 1939- (Beverly Hills, CA : Metro-Goldwyn-Mayer, 2018)
In a dystopic future where a religion-based autocracy rules the country, women are second class citizens and after attempting to escape, June is sentenced to be a handmaid whose role is to bear children for childless government officials.
June -- Unwomen -- Baggage -- Other women -- Seeds -- First blood -- After -- Women's work -- Smart power -- The last ceremony -- Holly -- Postpartum -- The word.
Based on the novel by Margaret Atwood.
Dolby digital 5.1, wide screen 1.78:1.
Features: Season two : off book, Dressing dystopia.
Elisabeth Moss, Yvonne Strahovski, Max Minghella, Joseph Fiennes.
Originally broadcast on television in 2018.
TV rating: TV-MA.
Keywords: Atwood, Margaret, -- 1939- -- Television adaptations; Theocracy -- Drama; Misogyny -- Drama; Pregnancy -- Social aspects -- Drama; Dystopian television programs; Television series; Fiction television programs; Video recordings for the hearing impaired; Based on the book; Science fiction television programs